ISTH guidelines for treatment of thrombotic thrombocytopenic purpura - Zheng, X. Long (J Thromb Haemost, 2020)
BACKGROUND: Despite advances in treatment options for thrombotic thrombocytopenic purpura (TTP), there are still limited high quality data to inform clinicians regarding its appropriate treatment. METHODS: In June 2018, the ISTH formed a multidisciplinary guideline panel to issue recommendations about treatment of TTP. The panel discussed 12 treatment questions related to immune-mediated TTP (iTTP) and hereditary or congenital TTP (cTTP). The panel used the Grading of Recommendations Assessment, Development, and Evaluation approach, including evidence-to-decision frameworks, to appraise evidence and formulate recommendations. RESULTS: The panel agreed on 11 recommendations based on evidence ranging from very low to moderate certainty. For first acute episode and relapses of iTTP, the panel made a strong recommendation for adding corticosteroids to therapeutic plasma exchange (TPE) and a conditional recommendation for adding rituximab and caplacizumab. For asymptomatic iTTP with low plasma ADAMTS13 activity, the panel made a conditional recommendation for the use of rituximab outside of pregnancy, but prophylactic TPE during pregnancy. For asymptomatic cTTP, the panel made a strong recommendation for prophylactic plasma infusion during pregnancy, and a conditional recommendation for plasma infusion or a wait and watch approach outside of pregnancy. CONCLUSIONS: The panel’s recommendations are based on all the available evidence for the effects of an individual component of various treatment approaches, including suppressing inflammation, blocking platelet clumping, replacing the missing and/or inhibited ADAMTS13, and suppressing the formation of ADAMTS13 autoantibody. There was insufficient evidence for further comparing different treatment approaches (eg, TPE, corticosteroids, rituximab, and caplacizumab, etc.), for which high quality studies are needed.